2021
DOI: 10.31620/jccc.12.21/08
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Social Media Marketing Features and Brand Loyalty in the Fast Food Industry

Abstract: The key objective of this research was to test the role of social media marketing features (interactivity, perceived relevance, entertainment, and informativeness) in affecting brand loyalty in the fast-food industry. The required data was obtained through a quantitative survey from customers of fast-food brands in the United Arab Emirates. The findings revealed that most of the social media marketing features positively influence brand loyalty. In detail, it was found that interactivity and perceived relevanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…Prior research has found that the social elements have an impact on the satisfaction of the need for relatedness while teamwork boosts the desire to toil collectively for acquiring the main objectives (Sailer et al, 2017), and competition emboldens characters to strive toward a single motive (van Roy & Zaman, 2019), and interacting permits the consumers to stay connected. These current finding extends previous investigations on interactivity (Hanaysha et al, 2021), which specifies consumers play an active part while interacting with the situation/environment (van Noort et al 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Prior research has found that the social elements have an impact on the satisfaction of the need for relatedness while teamwork boosts the desire to toil collectively for acquiring the main objectives (Sailer et al, 2017), and competition emboldens characters to strive toward a single motive (van Roy & Zaman, 2019), and interacting permits the consumers to stay connected. These current finding extends previous investigations on interactivity (Hanaysha et al, 2021), which specifies consumers play an active part while interacting with the situation/environment (van Noort et al 2012).…”
Section: Discussionsupporting
confidence: 89%
“…In fact, it can be very effectively used for promoting health practices among the masses at even individual levels (Syed-Abdul et al, 2016). It can be a great tool to reach out to the target population (Hanaysha et al, 2021) at individual level with personalized messages as well as a source of knowledge sharing too (Sharma, 2021). Researchers found that young population uses SNSs quite regularly, particularly Facebook, for collecting news and information, search facts and be aware of environmental issues too (Rahim & Jalaladeen, 2016).…”
Section: Social Networking Sitesmentioning
confidence: 99%
“…assessment to ascertain the relationships hypothesized between the constructs (Hanaysha et al, 2021;Rashid et al, 2022).…”
Section: Figure -1: Conceptual Modelmentioning
confidence: 99%